Is financial inclusion good for bank stability? International evidence - Ahamed, M. Mostak; Mallick, Sushanta K. (Journal of economic behavior & organization, 2019)
Financial inclusion has become an important public policy priority following the recent global financial crisis. Yet, we know very little of how it impacts soundness of the providers of financial services. Using an international sample of 2635 banks in 86 countries over the period 2004–12, we find that higher level of financial inclusion contributes to greater bank stability. The positive association is particularly pronounced with those banks that have higher customer deposit funding share and lower marginal costs of providing banking services; and also with those that operate in countries with stronger institutional quality. The results are robust to instrumental variables analysis, controlling for bank fixed effects, alternative measures of financial inclusion, among several other robustness tests. Our results highlight that the importance of ensuring inclusive financial system is not only a development goal but also an issue that should be prioritised by banks, as such a policy drive is good for their stability.